Women’s awareness of positions for a normal birth - Silveira, Isolda Pereira da; Carvalho, Francisca Ana Martins (Rev Rene, 2003)
This is a study, which shows the level of awareness of parturient for positions for a normal birth. The data was collected in the months of April and June of 2000 at the obstetrical center of the maternity school Assis Chateaubriand in Fortaleza. 86 parturient women attended by nurses were used to collect data. It showed that 38% of women were familiar with a sitting position, 21% with the laying down position and 9% with the squatting position. The data also showed that 18% of them lacked knowledge for all the positions. We find most important to direct women towards the position of their choice.